1996
DOI: 10.1002/(sici)1096-9098(199612)63:4<221::aid-jso2>3.3.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Calcification in colorectal hepatic metastases correlates with longer survival

Abstract: Background: Calcification occurs in 12-27% of hepatic colorectal metastases, but its clinical significance and its influence on prognosis are unknown.Methods: All patients diagnosed with colorectal liver metastases at the Ottawa Regional Cancer Centre in 1991 (n = 97), as well as those enrolled in chemotherapy trials in [1990][1991][1992] (n = 51), were entered into a retrospective cohort study. Thirty-six patients were excluded due to inadequate follow-up. In the remaining 112, abdominal CT scans and/or ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The increased calcification may indicate that chemotherapy has been effective. Easson et al [ 21 ] reported that the presence of calcifications within a colorectal liver metastasis indicate a markedly improved prognosis. Burkill et al [ 22 ] reported that patients with noncalcified ovarian cancers survive longer than the patients with calcified tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The increased calcification may indicate that chemotherapy has been effective. Easson et al [ 21 ] reported that the presence of calcifications within a colorectal liver metastasis indicate a markedly improved prognosis. Burkill et al [ 22 ] reported that patients with noncalcified ovarian cancers survive longer than the patients with calcified tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] In particular, it has also been reported that calcification in the tumor and regional lymph nodes can be considered a benign prognostic factor in colorectal cancer and lung cancer. [ 7 ] Calcification may be associated with tumor cell death, but the intrinsic cause of cell death remains unknown. These findings inspired us to investigate whether the local enrichment of Ca 2+ in tumor foci can promote the development of tumor calcification, a hypothesis that could have potential for the early identification of solid tumors.…”
Section: Introductionmentioning
confidence: 99%